Development of a miRNA-based diagnostic assay for pancreatic ductal adenocarcinoma. (April 2011) - Szafranska-Schwarzbach, Anna E; Adai, Alex T; Lee, Linda S; Conwell, Darwin L; Andruss, Bernard F
Diagnosis of pancreatic cancer remains a clinical challenge. Both chronic pancreatitis and pancreatic cancer may present with similar symptoms and similar imaging features, often leading to incorrect interpretation. Thus, the use of an objective molecular test that can discriminate between chronic pancreatitis and pancreatic cancer will be a valuable asset in obtaining a definitive diagnosis of pancreatic cancer. Following Clinical Laboratory Improvement Amendments and College of American Pathologists guidelines, Asuragen Clinical Services Laboratory has developed and validated a laboratory-developed test, miRInform ®® Pancreas, to aid in the identification of pancreatic ductal adenocarcinoma. This molecular diagnostic tool uses reverse-transcription quantitative PCR to measure the expression difference between two miRNAs, miR-196a and miR-217, in fixed tissue specimens. This article describes the test validation process as well as determination of performance parameters of miRInform Pancreas.